A revision of the South American bee genus Leptometriella Roig-Alsina (Hymenoptera, Apidae, Emphorini) - Roig Alsina, Arturo Hernan (2008)
A revision of the emphorine bee genus Leptometriella Roig-Alsina is presented. These bees occur mostly in xeric areas of South America, from Cochabamba in Bolivia to northern Patagonia in Argentina. Seven species are recognized, four of which are described as new: L. boliviana and L. minima from Bolivia, and L. hirsutula and L. monteana from Argentina. Lectotypes are designated for Teleutemnesta separata Holmberg, 1903, and Ancyloscelis minuta Friese, 1908. Ancyloscelis humilis Vachal, 1904, Ancyloscelis minuta Friese, 1908, and Melitoma specularis Vachal, 1909, are new synonyms of L. separata (Holmberg). A key to the species, descriptions, and illustrations are provided.